The Effect of Mouthrinses on Surface Roughness of Two Nanohybrid Resin Composites - Yilmaz, Emre; Mujdeci, Arzu (Brazilian Dental Science, 2021)
Objective: The aim of this study was to evaluate the effect of four different mouthrinses on the surface roughness of two nanohybrid resin composites. Material and Methods: Fifty samples were prepared for each of the resin composites (2x8 mm) and a profilometer was used to determine the initial surface roughness (Ra) of each sample. Then, they were divided into 5 subgroups (n= 10), and exposed to the following mouthrinses (12h, 37 ºC): containing alcohol and essential oils; alcohol and chlorhexidine; alcohol-free and essential oils; alcohol free and cetil prydinium chlorite; or distilled water (control). The surface roughness of each sample was measured again. Statistical analyses of the data were performed via two-way ANOVA and Bonferroni tests. Results: Overall, statistically significant differences were not found between the resin composites (p> 0.05), but significant differences were found among the mouthrinses (p< 0.05). Interactions between the mouthrinses and the resin composites was statistically significant (p< 0.05). Both of the resin composites had the highest surface roughness after exposure to mouthrinse with alcohol and essential oils (p< 0.05), followed by mouthrinse with alcohol and chlorhexidine. Both alcohol-free mouthrinses caused surface roughness either similar to distilled water (p> 0.05) or lower than distilled water (p< 0.05) on the nanohybrid resin composites used. Conclusion: The mouthrinses affected the surface roughness of the resin composites in different ways. This was dependent on mouthrinse contents and the chemical structure of the resin composites. Alcohol-containing mouthrinses caused the most changes in the surface roughness of both resin composites. Keywords Alcohol; Chlorhexidine; Composite resin; Essential oil; Roughness.